Monitoring of elastic properties of concrete since very early age by means of cyclic loadings, ultrasonic measurements, natural resonant frequency of composite beam (EMM-ARM) and with smart aggregates - Boulay, C. (2013)
Early age cracking of structures often leads to aesthetic problems and service life reduction. Among the parameters involved in the stress build-up that causes this cracking process, the stiffness evolution is of major importance for models and numerical computations. This paper reports the use of six different techniques aimed for stiffness evolution assessment, applied on the same concrete mix, in a round robin experimental test within three laboratories. The observations are compared after having expressed the results at the same maturity. Some of the reported techniques provide original means for Young’s modulus monitoring of concrete at early age both for industrial and research applications. Two sets of results emerge. Ultrasonic measurements provide values of Young's modulus much higher than the values provided by the static or quasi static tests at the time of the concrete setting. This difference decreases as the concrete hardens.